Usable and Accessible Design Features in Malaysian Houses for the Independent Aged - Mansor, Noranita (2008)
Most houses built today will most likely be occupied in the next fifty years. The houses that people choose to reside in are unchanged and often tend to disregard the changes in people’s life especially toward age and ability. For that reason, this research attempts to evaluate the existing design features in house environment to accommodate life transitions as the population grows by using Universal Design (UD). UD is an integrated, inclusive and creative form of design that evaluates whether design features in house environment are usable and accessible for a diverse population by a set of seven principles. The UD principles are adopted as the theoretical framework in this research. The case study method was used in this research consisting of six purposive non-random samples selected from residents residing at a local housing development in Malaysia as the unit of analysis. The residents of these units average fifty-five and above in age and have resided their homes since 1980-1985. Three stages of data collection were used to link the findings to the proposition. They are i) In depth interview, ii) Site Survey Checklist with Walk-Through Observation and iii) Universal Design Performance Measure. Findings from the research shows that the existing design features tend to generate problems to the residents as their physical abilities change with age. Hence, this research concludes that there is need for a new design approach basing on UD for creating usable and accessible design features to support people living independently in their chosen environment as they age. The results are expected to become the basis for housing professionals, architects, interior designers, policy-makers in future environmental design for the aging population. Future studies are recommended to develop a UD performance measure for Malaysia that could address the need to support the growing aged population in the country.